5-azacytidine reactivates pluripotency gene expression, affects TET2 and histone transcription and modifies chromatin organization and morphology of mammal skin fibroblasts (International Journal of Health, Animal Science and Food Safety, 2016)
Phenotype expression is controlled by epigenetic regulations that guide cells through differentiation.The process is reversible and cells can be driven back to a higher plasticity state with the use ofepigenetic modifiers. In this work we exposed skin fibroblasts to the demethylating agent 5-azacytidine(5-aza-CR), which is a well-known DNA methyltransferase inhibitor, and has been recently shown toincrease cell plasticity and facilitate phenotype changes in different cell types (Pennarossa, 2013; Brevini,2014; Pennarossa, 2014; Brevini, 2016). Although many aspects controlling its demethylating action havebeen widely investigated, the mechanisms through which 5-aza-CR acts on cell plasticity are still poorlyunderstood. At the end of 5-aza-CR treatment, cells were divided in three experimental groups andcultured for 24 and 48 hours: A) cells were returned in standard fibroblast medium; B) cells werecultured in medium specific for pluripotency maintenance; C) cells were placed in a mediumencouraging pancreatic differentiation. At the end of the culture period, as expected, we could observea global demethylating effect. In parallel, however we detected a transient upregulation of thepluripotency genes OCT4, NANOG and REX1. Increased transcription of TET2 and histones belonging tothe 1,2,3 and 4 families, together with changes in the expression of enzymes controlling histoneacetylation were also appreciated. Interestingly, these results were accompanied by morphological andultrastructural changes as well as by chromatin structure modifications. All together our findingsindicate that 5-aza-CR induced somatic cell transition to a higher plasticity state involves novel cellulartargets that activate multiple epigenetic regulatory pathways.
Keywords: Epigenetic; 5-aza-CR; Methylation; Plasticity; TET genes; Histone